2022
DOI: 10.1038/s41467-022-34557-2
|View full text |Cite
|
Sign up to set email alerts
|

Host biology, ecology and the environment influence microbial biomass and diversity in 101 marine fish species

Abstract: Fish are the most diverse and widely distributed vertebrates, yet little is known about the microbial ecology of fishes nor the biological and environmental factors that influence fish microbiota. To identify factors that explain microbial diversity patterns in a geographical subset of marine fish, we analyzed the microbiota (gill tissue, skin mucus, midgut digesta and hindgut digesta) from 101 species of Southern California marine fishes, spanning 22 orders, 55 families and 83 genera, representing ~25% of loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 101 publications
1
33
0
Order By: Relevance
“…reptiles, birds and mammals): while the latter are mainly dominated by Bacteroidetes and Firmicutes, the microbiome in fish is mainly composed of Proteobacteria and Firmicutes [12] (figure 1b). It has been shown that selective pressures arising from a wide range of host factors, including host anatomical features, play a unique role in the ecology of fish microbiomes [74]. Starting with the seminal study by Roeselers et al showing striking similarities between the gut microbial composition of laboratory-reared and wild-caught zebrafish [75], hostmediated selection of gut microbiome has been observed in many fish species, including European seabass (Dicentrarchus labrax), Atlantic cod (Gadus morhua), rainbow trout, salmon and several carp species (i.e.…”
Section: Anatomymentioning
confidence: 99%
“…reptiles, birds and mammals): while the latter are mainly dominated by Bacteroidetes and Firmicutes, the microbiome in fish is mainly composed of Proteobacteria and Firmicutes [12] (figure 1b). It has been shown that selective pressures arising from a wide range of host factors, including host anatomical features, play a unique role in the ecology of fish microbiomes [74]. Starting with the seminal study by Roeselers et al showing striking similarities between the gut microbial composition of laboratory-reared and wild-caught zebrafish [75], hostmediated selection of gut microbiome has been observed in many fish species, including European seabass (Dicentrarchus labrax), Atlantic cod (Gadus morhua), rainbow trout, salmon and several carp species (i.e.…”
Section: Anatomymentioning
confidence: 99%
“…However, for this and other parasites, we are yet to fully understand if there is a differential response at a molecular level in reaction to parasite species or community, haplotype composition, site of entry and site of infections. Host–parasite–microbiome interaction and probiotic search are other areas, which highly benefit from advancements in genomic technologies, and will likely be more frequently addressed in the near future (Minich et al, 2022). Perch skin and gut microbiome shows high inter‐individual variability and sex‐dependent patterns and is influenced by intrinsic and extrinsic environmental factors (Berggren et al, 2022; Chen, Hou, et al, 2022; Kashinskaya et al, 2020; Zha et al, 2018).…”
Section: Areas Where Omics Are Expected To Improve Understanding Of P...mentioning
confidence: 99%
“…available nutrients and suitable habitat) resulting in a mutualistic relationship with the host. This provides the context for a unique coevolved process in which host and their gut microbiome interact in a mutualistic adaptive scenario (Escalas et al, 2021; Groussin et al, 2020; Minich et al, 2022). Coevolution is defined as the reciprocal adaptation process experienced by two organisms as the result of their reciprocal selection pressures; it is possible for the microbiome to evolve at the individual species level, as well as a community response to host‐mediated selection (Koskella & Bergelson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all animals examined to date show complex interactions with their associated microbial communities. It is evident that there are bidirectional interactions between the gut microbiome and the host in humans (Davison et al, 2017;Dayama et al, 2020;Meisel et al, 2018) and non-human animals (Fuess et al, 2021;Muehlbauer et al, 2021;Naya-Catala et al, 2021). These interactions affect a wide range of host phenotypes including metabolism, immunity and physiology (McFall-Ngai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%